Procedures adopted by orthodontists for space closure and anchorage control - André da Costa Monini; Luiz Gonzaga Gandini Júnior; Ary dos Santos-Pinto; Luiz Guilherme Martins Maia; Willian Caetano Rodrigues (Dental Press Editora, 2013)
OBJECTIVE: The aim of this study was to identify the procedures adopted by Brazilian orthodontists in the following situations: extraction space closure, anchorage control in case of necessary anchorage for group A and frequency of skeletal anchorage use, especially in the upper jaw. METHOD: A questionnaire was sent to the e-mail address of all dentists registered in the Brazilian Federal Council of Dentistry. RESULTS: The results showed that most Brazilian orthodontists usually perform extraction space closure by means of sliding mechanics. The use of palatal bar, inclusion of second molars in the archwire and space closure performed in two phases are the most used techniques for anchorage control in the upper jaw. The skeletal anchorage is referenced by 36.5% of specialists as a routine practice for the upper jaw anchorage. CONCLUSIONS: There is a wide variety of procedures adopted by Brazilian orthodontists for orthodontic space closure and anchorage control.